STRANGE STARS AT VACUUM PRESSURE DEPENDENT ON QUARK DENSITY: ERRATUM: https://doi.org/10.46991/PYSU:A/2018.52.1.068Proc. YSU A: Phys. Math. Sci. 52 (2018), 68 - Vartanyan, Yu.L.; Grigoryan, A.K.; Shahinyan, H.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
Equation of state of strange quark matter has been studied in the framework of MIT bag model, when vacuum pressure B depends on concentration of baryons n. The actuality of such studies is conditioned by the increasing of quark matter density from surface to star center. In the literature there exist different representations of function B(n). In the present work Gaussian parametrization is used, which is based on the idea of existence of asymptotic limiting value of this parameter. For four groups of parameters the equations of state of quark matter were determined. The main integral parameters of star configurations were obtained by numerically integrating of star equilibrium equations (the TOV equation). In the considered case it turns that when vacuum pressure dependence on concentration of baryons is taken into account, configurations of strange stars have maximal masses less than two solar masses.